2020
DOI: 10.1177/2470547020944553
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and Amygdalar Volume Changes in Major Depressive Disorder: A Targeted Review and Focus on Stress

Abstract: Medial temporal lobe structures have long been implicated in the pathogenesis of major depressive disorder. Although findings of smaller hippocampal and amygdalar volumes are common, inconsistencies remain in the literature. In this targeted review, we examine recent and significant neuroimaging papers examining the volumes of these structures in major depressive disorder. A targeted PubMed/Google Scholar search was undertaken focusing on volumetric neuroimaging studies of the hippocampus and amygdala in major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 98 publications
2
37
1
Order By: Relevance
“…The experiential aspects of MDD theoretically map onto brain limbic circuitry, in particular the subcortical temporal lobe limbic structures of the hippocampus and the amygdala ( Kaiser et al, 2015 , Pruessner et al, 2010 ). Evidence indicates that state depression is associated with reduced hippocampal volumes ( Brown et al, 2014 , Nolan et al, 2020 , Schmaal et al, 2016 , Stephanie Campbell et al, 2004 , Wise et al, 2017 ). Hippocampal pathology is consistent with the key cognitive difficulties experienced in MDD, such as impairments in short term and autobiographical memory formation ( Kohler et al, 2015 ) and attentional problems ( Disner et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The experiential aspects of MDD theoretically map onto brain limbic circuitry, in particular the subcortical temporal lobe limbic structures of the hippocampus and the amygdala ( Kaiser et al, 2015 , Pruessner et al, 2010 ). Evidence indicates that state depression is associated with reduced hippocampal volumes ( Brown et al, 2014 , Nolan et al, 2020 , Schmaal et al, 2016 , Stephanie Campbell et al, 2004 , Wise et al, 2017 ). Hippocampal pathology is consistent with the key cognitive difficulties experienced in MDD, such as impairments in short term and autobiographical memory formation ( Kohler et al, 2015 ) and attentional problems ( Disner et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…While increased amygdala activation was observed in patients with bipolar disorder across all illness phases, similar findings were also observed during attention tasks that had no emotional components, suggesting the additional role of the amygdala in cognition [286]. A recent meta-analysis reported smaller amygdala volumes in participants with major depressive disorder (MDD) compared to healthy controls, although greater differences between groups were observed for hippocampal volume [287]. Interestingly, amygdala volumes in bipolar patients did not differ from healthy controls [288].…”
Section: The Role Of the Amygdala In Sensation Seeking Psychosis Major Depression And Other Psychiatric Disordersmentioning
confidence: 79%
“…For example, previous studies of the amygdala and hippocampus have reported reduced volume as a potential biomarker of depression (Roddy et al, 2019;Sheline et al, 2019). According to 12 studies reported so far, a 5.2% decrease in the left amygdala and a 7.4% decrease in the right amygdala have been reported in depression (Nolan et al, 2020). Notwithstanding, there are fewer reports on amygdala volume than on hippocampal volume, and there is a lack of assessment of the amygdala in relation to depression.…”
Section: Introductionmentioning
confidence: 99%